PENGARUH HOME CARE TERHADAP KEBERSIHAN GIGI DAN MULUT SISWA TUNANETRA DI SLB A YAPTI MAKASSAR - Feblina, Ayu Rahayu; Alfah, Siti; Sangkala, Sangkala; Zulkarnain, Zulkarnain (Jurnal Ilmiah Amanah Akademika, 2022)
Background. Four factors that can influence tooth and mouth cleanliness of person are genetic, invironment (physical or sociocultural), behavior, and health services. According to WHO, 90% of 5-year-old students was free from dental caries as much 361.860 students and 317.016 among them were students with special need (range 5-8 year-old). There were 66.610 students with special need were registered at school for special need student. So there were 295.250 students with special need under supervision their parent and family but they did not get health services yet. Home care is the solution to improve tooth and maouth cleanliness of blind students. Methods. A quasi experimental design with one group pre test-post test design. Research occured during December 2022 at SLB A Yapti Makassar. There were 24 samples that all amount of SLB A Yapti Makassar students. The samples were got by sampling technique with total sample (taking all of amount of populations). Data was analized by SPSS 17.0 for Windows. Result. There were significant effect of home care to tooth and mouth of blind students at SLB A Yapti Makassar. It was shown by result of one group pre test and post test tooth and mouth cleanliness p= 0.00 (p< 0,005) and IK= 95% was between 0,31-0,63. Conclution. There were significant effect of home care to tooth and mouth of blind students at SLB A Yapti Makassar.